Child and maternal attachment predict school‐aged children's psychobiological convergence. Issue 8 (24th June 2018) - Sichko, Stassja; Borelli, Jessica L.; Smiley, Patricia A.; Goldstein, Alison; Rasmussen, Hannah F.
Abstract: Psychobiological convergence—the alignment of task‐related changes in children's self‐reported and physiological indices of reactivity—has recently emerged as a powerful correlate of children's attachment representations, but has not been explored for its association with children's self‐reported attachment, with parents' attachment, or with respect to cardiovascular reactivity. The present study found that, within a diverse community sample of mothers and school‐aged children ( N = 104, M age = 10.31), the positive link between cardiovascular (respiratory sinus arrhythmia [RSA]) and subjective reactivity to a stressor was only significant among children with high levels of security and children of mothers with low levels of attachment avoidance and anxiety. The convergence of children's subjective and physiological experience is discussed as a key developmental competence that may lay the groundwork for effective coping.